Are AI Health Screenings Affordable? A Deep Dive into the Economics of Digital Diagnostics - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Are AI Health Screenings Affordable? A Deep Dive into the Economics of Digital Diagnostics The integration of Artificial Intelligence (AI) into healthca...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Medical Imaging